2009
DOI: 10.1029/2008jd011659
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the ice phase in tropical altocumulus: SAMUM lidar observations over Cape Verde

Abstract: [1] The formation of the ice phase in tropical altocumulus has been studied with multiwavelength aerosol-cloud Raman lidar, wind Doppler lidar, and radiosonde, providing information on geometrical and optical properties, cloud phase, cloud top temperature, updraft and downdraft velocity, and fall speed of ice crystals. The observations were conducted at Praia (15°N, 23.5°W), Cape Verde, in the tropical North Atlantic in the framework of the Saharan Mineral Dust Experiment (SAMUM) project in January and Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
240
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(264 citation statements)
references
References 81 publications
(134 reference statements)
22
240
2
Order By: Relevance
“…Atmospheric observations indicate that heterogeneous ice nucleation in mixed-phase clouds can already occur at temperatures higher than −20 • C (Ansmann et al, 2009;Seifert et al, 2010;Kanitz et al, 2011). In contrast, laboratory studies showed that the majority of non-biological substances found in atmospheric ice crystal residues, i.e., natural mineral dust (e.g., Twohy and Poellot, 2005;Pratt et al, 2009;Kamphus et al, 2010), are only ice active at lower temperatures (e.g., Hoose and Möhler, 2012;Murray et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Atmospheric observations indicate that heterogeneous ice nucleation in mixed-phase clouds can already occur at temperatures higher than −20 • C (Ansmann et al, 2009;Seifert et al, 2010;Kanitz et al, 2011). In contrast, laboratory studies showed that the majority of non-biological substances found in atmospheric ice crystal residues, i.e., natural mineral dust (e.g., Twohy and Poellot, 2005;Pratt et al, 2009;Kamphus et al, 2010), are only ice active at lower temperatures (e.g., Hoose and Möhler, 2012;Murray et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Lidars are used since the 1970s to monitor clouds and their evolution, although primarily cirrus and mixed-phase clouds (Platt, 1973(Platt, , 1977Sassen, 1991). Our group also contributed to these observations over the last 25 years (Ansmann et al, 1993(Ansmann et al, , 2005Ansmann et al, 2009;Seifert et al, 2007Seifert et al, , 2010Seifert et al, , 2015Kanitz et al, 2011). Observations are rare in the case of liquid-water clouds because lidars are not appropriate for clouds with typical optical depths of 10 and more.…”
Section: Introductionmentioning
confidence: 97%
“…However, a number of field and modelling studies have indicated that in mixed-phase clouds water saturation is a prerequisite for the formation of ice, suggesting that deposition mode nucleation or condensation below water saturation may be of limited importance for such clouds (Field et al, 2012;Twohy et al, 2010;Ansmann et al, 2009;de Boer et al, 2011;Westbrook and Illingworth, 2011). Consequently both immersion and contact modes are expected to dominate ice formation in mixed-phase clouds (Hoose et al, 2010b).…”
Section: O'sullivan Et Al: Ice Nucleation By Fertile Soil Dustsmentioning
confidence: 99%